Phenotypic and molecular identification of Pantoea stewartii subspecies indologenes of mango (Mangifera indica L.) in Selangor - Ahmad Khashiri, Ahmad Mustakim (2017)
Mango (Mangifera indica L.) is among the most cultivated fruits in Malaysia, especially in the Northern regions with low rainfall rates. This fruit is produced for domestic and international market. However, a bacterium known as, Pantoea stewartii subspecies (spp.) indologenes can cause diseases in mango that are undetected until now. In general, the unknown diseases does not cause extreme losses, but in under favourable condition it can cause damages. Furthermore, symptoms showed by Pantoea stewartii spp. indologenes are similar as the bacterial black spot disease such as black scabby spots on the fruits. The objectives of this study were 1) to isolate and identify Pantoea spp. in local mango cultivars via phenotypic characterization, and 2) to determine the relationships of Pantoea stewartii spp. indologenes strains isolated in this study via molecular ii approaches. To achieve these objectives, infected mango fruits with bacterial black spot symptoms were obtained from Taman Pertanian Universiti UPM, Puchong, Selangor. In phenotypic characterization, the morphology of the bacterial strains isolated from the infected mango fruits were identified as yellow, slightly mucoid, mounded and circular in shape. Gram-staining revealed that all strains were Gram-negative with short rod-shaped. Pathogenicity test performed on mango seedlings of ‘Chok Anan’ variety with all strains induced symptoms that were damage on the upper side of the leaves and center of the leaves turned grey surrounded by a yellow halo. The PCR amplification of 16S rDNA region in all isolated strains produced an amplicon of ~1400 basepair (bp) in size. Sequencing analysis revealed that all strains were 99% identical to Pantoea stewartii spp. indologenes reference strains in GenBank database (Accession nos. HG792424 and HG792422). Phylogenetic analyses of 16S rDNA gene sequences further clustered all strains into Pantoea stewartii spp. indologenes reference sequences strains. To our knowledge, this is the first report of mango disease caused by Pantoea stewartii spp. indologenes in Malaysia.